Extraction of gaharu oil from karas (Aquilaria malaccensis) by using different solvents / Latifah Mohd Said, Nurul Amira Abd Aziz and Muhamad Iqram Ibrahim - Mohd Said, Latifah; Abd Aziz, Nurul Amira; Ibrahim, Muhamad Iqram (2009)
A research was done to study the extraction of gaharu oil from karas (Aquilaria malaccensis) by using different solvents. This research is done by two methods. The methods are water extraction and solvent extraction. For water extraction, there is one element namely hot water is used. While for solvent extraction, chemicals such as ethanol, methanol, toluene, acetone, ethyl acetate and petroleum benzene are used. The objectives of this research are to determine the most effective solvents to extract gaharu oil from Karas (Aquilaria malaccensis) and to study the effect of different solvents on oil yield. And the most suitable extraction of gaharu oil from karas wood is solvent extraction. It is because it can produce high yield ofoil and save production times. In fact, the gaharu oil has many uses such as perfume, aromatherapy and etc. This gaharu oil has high value in market.